Do anti‐IL‐6R blockers have a beneficial effect in the treatment of antibody‐mediated rejection resistant to standard therapy after kidney transplantation?. Issue 4 (13th December 2020) - Massat, Maéva; Congy‐Jolivet, Nicolas; Hebral, Anne‐Laure; Esposito, Laure; Marion, Olivier; Delas, Audrey; Colombat, Magali; Faguer, Stanislas; Kamar, Nassim; Del Bello, Arnaud; ,
Abstract : Antibody‐mediated rejection (AMR) that resists to standard of care (SOC) therapy remains a major challenge after kidney transplantation and leads to graft failure in a majority of cases. The use of anti‐IL6 receptor antibodies was suggested to treat chronic antibody‐mediated rejection (cAMR) after failure of classical treatments. We treated nine patients with AMR resistant to apheresis, rituximab, and intravenous immunoglobulins, with a monthly infusion of tocilizumab and compared them with a historical cohort of 37 patients with similar clinical, immunological, and histological characteristics. The 1‐year graft survival and the decline in renal function did not differ between patients who received tocilizumab and those who did not. Histological follow‐up showed that despite a decrease in inflammation and tubulitis scores after tocilizumab, the course of antibody‐mediated lesions and chronic glomerulopathy were similar in both groups. In our study, the addition of monthly infusions of tocilizumab did not alter the course of AMR that resist to SOC therapy. Large randomized studies are urgently needed to assess the effect of tocilizumab in this context. Abstract : Monthly infusion of tocilizumab for antibody‐mediated rejection resistant to standard‐of‐care therapy did not alter disease course compared to a historical cohort that received only standard‐of‐care therapy.